The Influence of Work Discipline and Incentives on Employee Performance: Study at PT. Bank KB Bukopin Syariah Samarinda Branch - Ervina Schoe; Marjoni Rachman; Titin Ruliana (Newinera Publisher, 2024)
The objective of this research is to examine the impact of work discipline and incentives on employee performance, with work motivation serving as an intervening variable, at PT Bank KB Bukopin Syariah Samarinda Branch. This research employs a quantitative methodology, using a sample of 83 informants, which represents the whole population of permanent workers of PT Bank KB Bukopin Syariah Samarinda Branch. The analytical tool used is SmartPLS version 3.2.9. PLS data analysis is conducted in two stages: evaluating the outer model, which is the measurement model, and evaluating the inner model, which is the structural model. The findings indicated a clear and substantial correlation between work discipline (X1) and work motivation (Z). Two incentives have a substantial and beneficial impact on job motivation. There is a strong and positive correlation between work discipline (X1) and employee performance (Y). The presence of incentives (X2) has a notable and constructive impact on the performance (Y) of employees. There is no correlation between work motivation (Z) and employee performance (Y). The combination of work discipline (X1) and rewards (X2) has a collective impact on work motivation. The combination of work discipline (X1) and incentives (X2) has a direct impact on employee performance. Employee performance (Y) is influenced by the combined impact of work discipline (X1), incentives (X2), and work motivation (Z). Work motivation cannot act as a mediator between Work Discipline (X1) and Employee Performance (Y). Work motivation cannot serve as a mediator between incentives (X2) and employee performance (Y).